Examining Financial Risk Contagion and Shock Response via Complex Network Analysis of Correlation and Causality in the Sports Industry - Wanying Du; Boyan Wang (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
In today's landscape of financial liberalization and economic integration, the sports industry is not immune to the complex interplay between financial and economic activities. This dynamic environment witnesses the frequent exchange of information within the sports financial market, resulting in a high degree of interaction. Such interaction has not only optimized the allocation of global financial resources in sports but has also amplified the repercussions and dissemination of financial crises within the sports sector. From the global sports financial system to individual sports entities, intricate relationships emerge in economic and financial activities among countries, forming a complex sports financial ecosystem. Understanding and characterizing the patterns of risk propagation and shock responses in the sports financial market is vital. It equips sports market participants and regulators with crucial market insights, aids in policy formulation, and enables proactive measures to prevent and address financial market crises within the sports industry. Considering the multifaceted interactions among various stakeholders in the sports financial market, this study adopts a complex network methodology to examine the dynamics of financial risk contagion and shock response, with a primary focus on the sports industry. This approach offers a valuable perspective, shedding light on the specific intricacies within the sports finance domain.